Investigating the Effect of Personality Traits on the Mental Health of Prisoners with the Mediation of Religiosity - Hamidi, Masoumeh; Khosravi, Sadrollah; Ebrahimi, Eshagh; Chinaveh, Mahboobeh (Shahroud Journal of Medical Sciences, 2025)
Background: Studies show that prisoners have a higher prevalence of mental disorders than the general population. Paying attention to factors affecting the mental health of prisoners, including religiosity and personality traits, is very important to reduce recidivism. This study aimed to investigate the relationship between mental health, personality traits, and religiosity in prisoners of Fars province.Methods: The study was correlational research conducted on all new prisoners in Shiraz. With Inclusion criteria have a willingness to participate in the survey, to have spent at least 48 hours in prison, and to have good mental health. Exclusion criteria included the presence of a mental disability, psychological problems, or being on medication . Demographic information, mental health, personality, and religiosity were assessed through face-to-face interviews, and relationships between variables were analyzed using structural equation modeling with SPSS 26 and AMOS 24.Results: Neuroticism through religiosity was associated with reduced depression, Somatic symptoms, social dysfunction, and anxiety. However, extraversion, openness to experience, agreeableness, and conscientiousness through religiosity are associated with increased depression, somatic symptoms, social dysfunction, and anxiety.Conclusions: personality traits indirectly impact mental health through religiosity, which plays a significant mediating role in these associations. Further research can examine how personality traits and religious beliefs work together to influence mental well-being.